The Meaning of Halal in The Food Industry in The Metaverse Era (A Comparison) - Susanti, Dyah Ochtorina; Sari, Nuzulia Kumala; Adonara, Firman Floranta; Tektona, Rahmadi Indra; Driss, Bakhouya (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The background of this research is that there are still many food products that have not been halal certified, even though the government through the Halal Product Guarantee Agency (BPJPH) has provided convenience in registering halal products online with free assistance. Especially in this metaverse era, where technology has developed rapidly so that the use of digital technology should be able to encourage development through the halal industry.Purposes of the Research: The purpose of this study, firstly, is to know and understand the meaning of halal in both Islamic law and the Civil Code. Second, understanding the halal industry in the metaverse era in terms of the theory of utilitarianism and Maqashid Sharia.Methods of the Research: This study uses a normative juridical method with a legal-statutory approach and a conceptual approach.Results of the Research: The results of this study are: First, that halal in Islamic Law and the Civil Code have different contexts, but have a similar meaning, namely referring to something that is permitted and not prohibited by law. Second, the halal industry based on utilitarianism has utility value both for business actors who register their food products, as well as for the general public as consumers. Furthermore, based on Maqashid Sharia, halal food is included in the category of protecting the soul (nafs) and protecting the mind (aql).